2001
DOI: 10.1016/s0893-133x(00)00167-6
|View full text |Cite
|
Sign up to set email alerts
|

CRH Signalling in the Bed Nucleus of the Stria Terminalis is Involved in Stress-Induced Cardiac Vagal Activation in Conscious Rats

Abstract: The bed nucleus of the stria terminalis (BNST) is involved in autonomic and behavioral reactions to fearful stimuli and contains corticotropin-releasing hormone (CRH) fibers and terminals. The role of CRH in the medial part of the BNST in the regulation of heart rate (HR) and PQ interval of theThe bed nucleus of the stria terminalis (BNST) is a rostral forebrain structure that is enclosed by the lateral ventricle, lateral septum, fornix, nucleus accumbens, preoptic area and hypothalamus. The BNST has been reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 36 publications
(35 reference statements)
1
56
0
3
Order By: Relevance
“…These observations are consistent with those of other reports showing increases in stress-like behaviors following intra-BNST infusions of CRF (Ciccocioppo et al 2003;Lee and Davis 1997;Liang et al 2001;Nijsen et al 2001). Anxiogenic-like effects of CRF were not observed in animals with erroneously placed microinjection needles outside of the BNST in regions such as the lateral hypothalamus, thalamus and nucleus accumbens, indicating a degree of anatomical specificity for the observed effects of CRF.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These observations are consistent with those of other reports showing increases in stress-like behaviors following intra-BNST infusions of CRF (Ciccocioppo et al 2003;Lee and Davis 1997;Liang et al 2001;Nijsen et al 2001). Anxiogenic-like effects of CRF were not observed in animals with erroneously placed microinjection needles outside of the BNST in regions such as the lateral hypothalamus, thalamus and nucleus accumbens, indicating a degree of anatomical specificity for the observed effects of CRF.…”
Section: Discussionsupporting
confidence: 92%
“…For example, intra-BNST administration of CRF facilitates the acoustic startle reflex , enhances retention of an inhibitory avoidance task (Liang et al 2001), produces anorectic effects (Ciccocioppo et al 2003) and tachycardia (Nijsen et al 2001). Conversely, infusions of nonselective CRF antagonists into the BNST produce anxiolytic-like and anti-stress effects, such as attenuated defensive burying behavior (Greenwell et al 2004), reduced conditioned freezing and stressinduced cardiovascular abnormalities (Nijsen et al 2001), and reduced conditioned defensivesubmissive behavior in response to social defeat (Jasnow et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that BST lesions disrupt contextual freezing in a previously shocked context (Onaka and Yagi, 1998;Nijsen et al, 2001;Sullivan et al, 2004;Resstel et al, 2008;Zimmerman and Maren, 2011), but not freezing to a conditioned cue nor fear-potentiated startle following cued fear conditioning (LeDoux et al, 1988;Walker et al, 2003). Very recently, we found that posttraining BST lesions completely disrupted the expression of contextual anxiety, as measured simultaneously with startle amplitude and freezing, in rats after reintroduction in a previously shocked context (Luyten et al, 2011c).…”
Section: Discussionmentioning
confidence: 63%
“…or directly into the BNST resulted in tachycardiac response, which was prevented either by β-adrenergic blockers or by CRH1R antagonists (Nijsen et al 2000). On the other hand, CRH, released in the medial BNST during conditioned fear stress, contributes to cardiac stress responses, particularly by activating vagal outflow (Nijsen et al 2001).…”
Section: Life Without Crh -From Paraventricular Lesions To Crh-ko Micmentioning
confidence: 99%